On MQTT Scalability in the Internet of Things: Issues, Solutions, and Future Directions - Spohn, Marco Aurélio (Journal of Electronics and Electrical Engineering, 2022)
The Publish/Subscribe (P/S) paradigm plays an essential role in developing Internet of Things (IoT) applications. Among the most representative P/S protocols, there is Message Queuing Telemetry Transport (MQTT). Standard implementations employ a single server acting as a broker for client-to-client communication: publishers send messages to the broker, which forwards them to the subscribers. A single server is a single point of failure and a potential bottleneck. Most IoT applications require a reliable and scalable communication system. MQTT systems can evolve in such requirements through clustering or federation of brokers, resulting in more complex communication architectures. This work presents an overview of current issues and solutions for addressing MQTT scalability in the IoT context.